ROAD TRAFFIC NOISE MAPPING BASED ON FIELD MEASUREMENTS IN LOCATION THAT DO NOT HAVE A STANDARDIZED MODEL IN ALGERIA - Boulemaredj, Ali; Amel, Saifi (Journal of Architecture&ENVIRONMENT, 2023)
The present study addresses the issue of noise pollution in Algeria due to road traffic and the possible preventive means and solutions for its abatement, in order to maintain an adequate sound environment in urban areas, especially next to residential ones. The main objective of this study aims at establishing an initial noise map for the Champs de Manoeuvre residential estate in Guelma; a medium-size city of Algeria, by adopting a research methodology that involved applying a quantitative investigation through carrying out field measurements during the winter and the summer season, three times for one week, from 9:00 am to 5:00 pm, using a sound level meter to measure and calculate the weighted equivalent continuous sound pressure level LAeq for 10min, the statistical level L10, the maximum sound level Lmax, the Traffic noise index TNI and the Noise pollution level NPL. The results obtained from the measurement campaign showed the extent of the noise levels produced from road traffic in the vicinity of the residential buildings in the studied area, emitted mainly from passing vehicles, acceleration and the irrational usage of horns, which led to a LAeq level of 74 dB at the source, thus, exceeding the 70 and 55 dB thresholds set in both of the Algerian noise regulation and the World Health Organization noise guidelines. Subsequently, implementation of the noise mapping technic can help in visualizing the spatio-temporal distribution of noise, in identifying its main sources and black spots in urban areas and in drawing up primary action plans for fighting against this issue.